2017
DOI: 10.1126/scisignal.aan6282
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein promotes bone destruction in human myeloma through the CD32–p38 MAPK–Twist axis

Abstract: Bone destruction is a hallmark of myeloma and affects 80% of patients. Myeloma cells trigger bone destruction by activating osteoclasts. We investigated the mechanism by which myeloma cells are regulated to do so. We found that C-reactive protein (CRP), a protein secreted in increased amounts by hepatocytes in response to myeloma-derived cytokines, activated myeloma cells to promote osteoclastogenesis and bone destruction in vivo. In mice bearing human bone grafts and injected with multiple myeloma cells, CRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
3
20
0
1
Order By: Relevance
“…49 High levels of circulating LDH enhanced myeloma cell proliferation and drug resistance under stressed conditions, and correlated with poor prognosis in myeloma. [50][51][52] More importantly, HR group correlated significantly to all the aforementioned parameters of disease activity, which support the fact that MMSP5 model might have prognostic value.…”
Section: Discussionsupporting
confidence: 67%
“…49 High levels of circulating LDH enhanced myeloma cell proliferation and drug resistance under stressed conditions, and correlated with poor prognosis in myeloma. [50][51][52] More importantly, HR group correlated significantly to all the aforementioned parameters of disease activity, which support the fact that MMSP5 model might have prognostic value.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that CRP-induced cytokine expression is also regulated by TWIST transcriptionally in myeloma cells (22). Results shown in Supplementary Figure S2 also clearly demonstrated that addition of CRP was capable of inducing TWIST via the CD32-dependent mechanism as addition of neutralizing antibodies against CD32 but not CD64 blocked CRP-induced TWIST expression by RA-FLSs.…”
Section: Crp Promotes Ra-fls To Produce Pro-inflammatory Cytokines Ansupporting
confidence: 57%
“…Recent data suggest that chronic inflammation and high CRP levels are associated with poor survival in renal cell, lung, pancreatic and breast cancer, in patients with head and neck cancer treated with radiotherapy and that CRP is associated with bone destruction in multiple myeloma. [3][4][5][6][7][8][9] CRP has been shown to supress T cell function in autoimmunity in mouse models and to suppress dendritic cell function in normals. 10 11 High CRP levels have been shown in small studies to be associated with a poor outcome with the use of the cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) blocking antibody tremelimumab.…”
mentioning
confidence: 99%